2012
DOI: 10.1002/j.2168-9830.2012.tb00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Framing Faculty and Student Discrepancies in Engineering Ethics Education Delivery

Abstract: Background The importance of ethics education in professional engineering preparation programs is well established, yet student outcomes remain mixed despite the efforts of engineering educators. Purpose (Hypothesis) A long line of research has suggested that students and faculty often have different perceptions of educational efforts and practices. In this study, we consider this as a potential reason for the continued mixed results of engineering ethics education by examining differing perceptions of faculty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 24 publications
3
61
0
Order By: Relevance
“…Perceptions also differ between respondents who have different primary functions within the educational equation. For example, as suggested by a history of research, faculty and students often perceive educational efforts and methods differently [29]. Therefore, perceptions between different stakeholders, i.e., students, faculty and industry, are likely to be varied [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceptions also differ between respondents who have different primary functions within the educational equation. For example, as suggested by a history of research, faculty and students often perceive educational efforts and methods differently [29]. Therefore, perceptions between different stakeholders, i.e., students, faculty and industry, are likely to be varied [27].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this is an area of particular importance as when considering that the history of research indicates that students and faculty do not share similar perceptions in regards to pedagogical methods and practice [29]. This has even greater emphasis when it comes to assessment, where large differences in the perceptions of students versus faculty were found when their perceptions of efficacy and usefulness of assessments of learning were explored [29].…”
Section: Discussionmentioning
confidence: 99%
“…Holsapple and colleagues concluded that students often have relatively narrow understandings of what qualifies as ethics compared to the faculties' beliefs in how ethics has been taught and demonstrated. 7 Loui explored students' perceptions of the characteristics and responsibilities of professional engineers as related to their professional identities. 8 Indeed, Zoltowski and colleagues found that students often struggled to identify "everyday" ethical considerations or issues within their design considerations or within their team processes.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…7,16 Nonetheless, a small but growing body of studies has investigated other foundational considerations, such as student perceptions of, and attitudes toward, social and ethical responsibility, as well as their levels of moral development. Beginning with broad perceptual considerations, a handful of studies have found that students often have rather narrow understandings of what counts as ethics, 17 while research by Zoltowski et al looking at views of ethics among members of project-based engineering teams revealed that students often had difficulties identifying "everyday" ethical considerations and issues, particularly in terms of design considerations, and issues to consider in their individual and group work processes. 18,20 The wider literature on ethical climate in organizations has additionally highlighted how social norms and culture can influence the behavior of individuals.…”
Section: Literature Reviewmentioning
confidence: 99%